A case of Plus minus lid syndrome with Hypesthesia- Hemiataxia - Ghosh, Sinjan; Guha, Gautam; Roy, Manoj Kumar; Bhattacharjee, Annesh; Repaka, Nikhil; Nanda, Sourav; Agasti, Niraja (Asian Journal of Medical Sciences, 2020)
We present the case of a patient with paramedian mesencephalic and ipsilateral thalamic infarction with an unusual clinical presentation, where the diagnosis and accurate anatomical localization were imperative for a unique clinicoradiological correlation. Our patient was a 42-years old, right-handed Indian gentleman with hypertension who presented following acute myocardial infarction. He developed acute diplopia, left ptosis and right eyelid retraction. There was an associated hemiataxia and diminished sensation in right half of body. Plus-minus lid syndrome and hemiataxia - hypesthesia are two different clinical syndromes. A co-association of these two syndromes in the same patient is rare which was evident in our case.